Factors Influencing Autopsy Decision in Deaths due to Road Accidents - Demirel, Birol; Akar, Taner; Özdemir, Çağlar; Cantürk, Nergis; Erdönmez, Filiz (The Bulletin of Legal Medicine, 2005)
Traffic accidents are the events resulting with death, injury and damage in which one or more vehicle and person, in motion or stationary, take part. Delivery of the death certificate following external examination without performing autopsy is a common practice in Turkey as shown in numerous studies. In this study, the crime scene investigation, external examination and autopsy reports of 54 subjects autopsied in Morgue Specialization Department of the Ankara Branch of the Council of Forensic Medicine between 01.01.1999-31.12.2003 were included. The study population were victims of traffic accident in central and peripheral district of Ankara. Subjects were evaluated with regard to age, sex, crime scene and time, the status at the time of crime (pedestrian, driver, passenger), death place, the qualification of the physician who did the death examination (specialist, general practitioner), cause of autopsy decision, cause of death and alcohol and drug levels. When evaluated according to autopsy causes; “determination of precise cause of death” was in the first rank with 19 subjects (35.2 %), “searching if there was a causality relation between the road accident and death” pursued with 11 subjects (20.4%). The precise cause of death was determined in 94.7% of the subjects for whom the autopsy was decided with a purpose of “determination of precise cause of death”, and in 72.7% of those questioned for causality relation. In conclusion; autopsy aids the forensic investigation and materialization of the justice for traffic accident victims. Therefore, we suggest that the public prosecutors should be more prone to deliver fatal traffic accidents to autopsy and thus the physicians should also strongly advise it in their preliminary reports. Key words: Traffic accident, death, autopsy.